Predicting big five personality traits from resting-state EEG connectivity: a connectome predictive modeling study - Chu Zhang; Yao Liu; Yiting Long; Siyuan Hu; Ming Li; Wenkai Bai; Yiting Li; Can Cui; Can Gao (Brain Structure and Function, 2026)

Brain-wide mapping and region-specific cellular characterization of Trhr1 reporter-labeled cells in mice using VISoR imaging - Mingrui Zhang; Su Ma; Hanbo Guo; Yuehan Ji; Hong Ni; Rongjing Ge; Yuanyuan Wang; Yong Jiang; Lianjun Li; Yuyang Zhu; Qian Wang; Lingxiao Guo; et al. (Brain Structure and Function, 2026)

Developmental trajectories of reading and neural substrates: a lifespan perspective on Chinese reading - Qianting Cheng; Hengyu Mao; Xinyang Liu; Xitong Liang; Yongbin Wei; Ting Qi; Li Liu (Brain Structure and Function, 2026)

Changes of network controllability and structural-function coupling in cerebral small vessel disease - Chengxia Liu; Tian Tian; Yuanyuan Qin; Shun Zhang; Yuanhao Li; Wenzhen Zhu (Brain Structure and Function, 2025)

Disrupted coordination between primary and high-order cognitive networks in Parkinson’s disease based on morphological and functional analysis - Yunxiao Ma; Li Wang; Ting Li; Jian Zhang; Shintaro Funahashi; Jinglong Wu; Xiu Wang; Kai Zhang; Tiantian Liu; Tianyi Yan (Brain Structure and Function, 2025)

Mapping sagittal-plane reference brain atlas of the cynomolgus macaque (Macaca fascicularis) based on consecutive cytoarchitectonic images - Yue Luo; Xiangning Li; Can Zhou; Guangcai Liu; Xueyan Jia; Xiaoquan Yang; Anan Li; Hui Gong; Zhao Feng (Brain Structure and Function, 2024)

MRI-based brain age prediction model for children under 3 years old using deep residual network - Lianting Hu; Qirong Wan; Li Huang; Jiajie Tang; Shuai Huang; Xuanhui Chen; Xiaohe Bai; Lingcong Kong; Jingyi Deng; Huiying Liang; Guangjian Liu; Hongsheng Liu; et al. (Brain Structure and Function, 2023)

Correction to: Quantitative susceptibility atlas construction in Montreal Neurological Institute space: towards histological‑consistent iron‑rich deep brain nucleus subregion identification - Chenyu He; Xiaojun Guan; Weimin Zhang; Jun Li; Chunlei Liu; Hongjiang Wei; Xiaojun Xu; Yuyao Zhang (Brain Structure and Function, 2023)

A comparative study of the superior longitudinal fasciculus subdivisions between neonates and young adults - Wenjia Liang; Qiaowen Yu; Wenjun Wang; Thijs Dhollander; Emmanuel Suluba; Zhuoran Li; Feifei Xu; Yang Hu; Yuchun Tang; Shuwei Liu (Brain Structure and Function, 2022)
The superior longitudinal fasciculus (SLF) is a complex associative tract comprising three distinct subdivisions in the frontoparietal cortex, each of which has its own anatomical connectivity and functional roles. However, many studies on white matter development, hampered by limitations of data quality and tractography methods, treated the SLF as a single entity. The exact anatomical trajectory and developmental status of each sub-bundle of the human SLF in neonates remain poorly understood. Here, we compared the morphological and microstructural characteristics of each branch of the SLF at two ages using diffusion MRI data from 40 healthy neonates and 40 adults. A multi-shell multi-tissue constrained spherical deconvolution (MSMT-CSD) algorithm was used to ensure the successful separation of the three SLF branches (SLF I, SLF II and SLF III). Then, between-group differences in the diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) metrics were investigated in all the SLF branches. Meanwhile, Mahalanobis distances based on all the diffusion metrics were computed to quantify the maturation of neonatal SLF branches, considering the adult brain as the reference. The SLF branches, excluding SLF II, had similar fibre morphology and connectivity between the neonatal and adult groups. The Mahalanobis distance values further supported the notion of heterogeneous maturation among SLF branches. The greatest Mahalanobis distance was observed in SLF II, possibly indicating that it was the least mature. Our findings provide a new anatomical basis for the early diagnosis and treatment of diseases caused by abnormal neonatal SLF development.

Quantitative susceptibility atlas construction in Montreal Neurological Institute space: towards histological-consistent iron-rich deep brain nucleus subregion identification - Chenyu He; Xiaojun Guan; Weimin Zhang; Jun Li; Chunlei Liu; Hongjiang Wei; Xiaojun Xu; Yuyao Zhang (Brain Structure and Function, 2022)

Medial prefrontal and occipito-temporal activity at encoding determines enhanced recognition of threatening faces after 1.5 years - Xiqin Liu; Xinqi Zhou; Yixu Zeng; Jialin Li; Weihua Zhao; Lei Xu; Xiaoxiao Zheng; Meina Fu; Shuxia Yao; Carlo V. Cannistraci; Keith M. Kendrick; Benjamin Becker (Brain Structure and Function, 2022)

The selective contributions of right cerebellar lobules to reading - Hehui Li; Rebecca A. Marks; Lanfang Liu; Xiaoxia Feng; Manli Zhang; Feng Ai; Yue Gao; Mengyu Tian; Xiujie Yang; Jia Zhang; Hejing Zhong; Li Liu; et al. (Brain Structure and Function, 2022)

Postnatal development of BAG3 expression in mouse cerebral cortex and hippocampus - Xinlu Li; Geng Lin; Tongtong Liu; Ning Zhao; He Xu; Huaqin Wang; Wei Zheng (Brain Structure and Function, 2021)

Mapping fetal brain development based on automated segmentation and 4D brain atlasing - Haotian Li; Guohui Yan; Wanrong Luo; Tingting Liu; Yan Wang; Ruibin Liu; Weihao Zheng; Yi Zhang; Kui Li; Li Zhao; Catherine Limperopoulos; Yu Zou; et al. (Brain Structure and Function, 2021)

Reduced listener–speaker neural coupling underlies speech understanding difficulty in older adults - Lanfang Liu; Xiaowei Ding; Hehui Li; Qi Zhou; Dingguo Gao; Chunming Lu; Guosheng Ding (Brain Structure and Function, 2021)

Connective profiles and antagonism between dynamic and static connectivity underlying generalized epilepsy - Sisi Jiang; Hechun Li; Haonan Pei; Linli Liu; Zhiliang Li; Yan Chen; Xiangkui Li; Qifu Li; Dezhong Yao; Cheng Luo (Brain Structure and Function, 2021)

An investigation of the neural association between auditory imagery and perception of complex sounds - Jin Gu; Hairuo Zhang; Baolin Liu; Xianglin Li; Peiyuan Wang; Bin Wang (Brain Structure and Function, 2019)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Top-down control of the medial orbitofrontal cortex to nucleus accumbens core pathway in decisional impulsivity - Zhiyan Wang; Lupeng Yue; Cailian Cui; Shuli Liu; Xuewei Wang; Yijing Li; Longyu Ma (Brain Structure and Function, 2019)

Individual differences in inhibitory control abilities modulate the functional neuroplasticity of inhibitory control - Mo Chen; Yan Jing Wu; Junjie Wu; Yongben Fu; Shuhua Li; Huanhuan Liu; Chunming Lu; Taomei Guo (Brain Structure and Function, 2019)

Genetic labeling reveals temporal and spatial expression pattern of D2 dopamine receptor in rat forebrain - Qing Yu; Ying-Zi Liu; Yan-Bing Zhu; Yao-Yi Wang; Qian Li; Dong-Min Yin (Brain Structure and Function, 2019)

Discover mouse gene coexpression landscapes using dictionary learning and sparse coding - Yujie Li; Hanbo Chen; Xi Jiang; Xiang Li; Jinglei Lv; Hanchuan Peng; Joe Z. Tsien; Tianming Liu (Brain Structure and Function, 2017)

Commonly preserved and species-specific gyral folding patterns across primate brains - Xiao Li; Hanbo Chen; Tuo Zhang; Xiang Yu; Xi Jiang; Kaiming Li; Longchuan Li; Mir Jalil Razavi; Xianqiao Wang; Xintao Hu; Junwei Han; Lei Guo; et al. (Brain Structure and Function, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

SMN is required for the maintenance of embryonic stem cells and neuronal differentiation in mice - Wei-Fang Chang; Jie Xu; Chia-Chun Chang; Shang-Hsun Yang; Hsin-Yang Li; Hsiu Mei Hsieh-Li; Mong-Hsun Tsai; Shinn-Chih Wu; Winston T. K. Cheng; Ji-Long Liu; Li-Ying Sung (Brain Structure and Function, 2015)

DISC1 Ser704Cys impacts thalamic-prefrontal connectivity - Bing Liu; Lingzhong Fan; Yue Cui; Xiaolong Zhang; Bing Hou; Yonghui Li; Wen Qin; Dawei Wang; Chunshui Yu; Tianzi Jiang (Brain Structure and Function, 2015)

A functional model of cortical gyri and sulci - Fan Deng; Xi Jiang; Dajiang Zhu; Tuo Zhang; Kaiming Li; Lei Guo; Tianming Liu (Brain Structure and Function, 2014)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Diffusion tensor imaging reveals evolution of primate brain architectures - Degang Zhang; Lei Guo; Dajiang Zhu; Kaiming Li; Longchuan Li; Hanbo Chen; Qun Zhao; Xiaoping Hu; Tianming Liu (Brain Structure and Function, 2013)

Regional and cell-type specific distribution of HDAC2 in the adult mouse brain - Zhi-Gang Yao; Ling Zhang; Lan Huang; Hua Zhu; Ying Liu; Chun-Mei Ma; Shu-Li Sheng; Chuan Qin (Brain Structure and Function, 2013)